Optimasi Produksi Gula Merah Menggunakan Metode Simpleks - Rizal, Rizal; Wahyudien, Mohammad Arief Nur; Ahistasari, Asih; Tajuddin, Tamrin; Maulana, Mirga Maulana (Industrial Engineering Journal – System, 2023)
The PWJ Brown Sugar Factory is one of the MSME industries which operates in the F&Bproduction sector, mainly brown sugar production. Sales at this factory often change every month.Therefore, it is necessary to plan production quantities so there are no excesses or shortages whenproducing brown sugar. According to available resources, this research aims to optimizeproduction and profits in making brown sugar at the PWJ Brown Sugar Factory. To maximizeprofits, the simplex linear programming method will be used. The linear programming methodhelps companies by combining product variations based on the company's limited resources. Inthis research, the data calculation process to maximize profits was carried out using the MicrosoftExcel application. Data collection carried out in this research was through direct interviews withbrown sugar factory owners in the Sorong Regency area. Next, the data is processed using alinear program, especially the simplex method. This research discusses two types of brown sugar:type A and type B. The price of brown sugar in this factory is 18,000-22,000/kg. The maximumprofit at the PWJ Brown Sugar Factory will be obtained when producing 15 kilograms of type Abrown sugar and 12kg of type B with a total income of Rp. 546,000-. This research can still bedeveloped, so it is recommended for future researchers to use other applications as comparisonmaterial.